Retromer dependent changes in cellular homeostasis and Parkinson's disease. Issue 7 (22nd December 2021) - Yang, Zhe; Li, Zebin; Teasdale, Rohan D.
Abstract: To date, mechanistic treatments targeting the initial cause of Parkinson's disease (PD) are limited due to the underlying biological cause(s) been unclear. Endosomes and their associated cellular homeostasis processes have emerged to have a significant role in the pathophysiology associated with PD. Several variants within retromer complex have been identified and characterised within familial PD patients. The retromer complex represents a key sorting platform within the endosomal system that regulates cargo sorting that maintains cellular homeostasis. In this review, we summarise the current understandings of how PD-associated retromer variants disrupt cellular trafficking and how the retromer complex can interact with other PD-associated genes to contribute to the disease progression.